Impact of maternal diet on human milk composition and neurological development of infants. Issue 3 (5th February 2014) - Innis, Sheila M
ABSTRACT: Maternal nutrition has little or no effect on many nutrients in human milk; for others, human milk may not be designed as a primary nutritional source for the infant; and for a few, maternal nutrition can lead to substantial variations in human milk quality. Human milk fatty acids are among the nutrients that show extreme sensitivity to maternal nutrition and are implicated in neurological development. Extensive development occurs in the infant brain, with growth from 350 g at birth to 925 g at 1 y, with this growth including extensive dendritic and axonal arborization. Transfer of n–6 (omega-6) and n–3 (omega-3) fatty acids from the maternal diet into human milk occurs with little interconversion of 18:2n–6 to 20:4n–6 or 18:3n–3 to docosahexaenoic acid (DHA) and little evidence of mammary gland regulation to maintain individual fatty acids constant with varying maternal fatty acid nutrition. DHA has gained attention because of its high concentrations and roles in the brain and retina. Studies addressing DHA intakes by lactating women or human milk amounts of DHA at levels above those typical in the United States and Canada on infant outcomes are inconsistent. However, separating effects of the fatty acid supply in gestation or in the weaning diet from effects on neurodevelopment solely due to human milk fatty acids is complex, particularly when neurodevelopment is assessed after the period of exclusive human milk feeding. Information on infant fatty acid intakes, including milk volume consumed and energy density, will aid in understanding of the human milk fatty acids that best support neurological development.